The Effect of Policy Implementation, Leadership, Financial Institutions, Community Participation in Mining Management on Community Welfare in Education - Mimpin Sitepu (Syntax Corporation Indonesia, 2024)
The purpose of this study was to determine the effect of policy implementation, leadership, financial institutions, community participation in mining management, on community welfare in education. This research was conducted in the Bangka Belitung Islands Province as a case study. The research design used was descriptive analytic design followed by sampling using the Stratified Random Sampling technique with a total of 452 respondents and data analysis with simple and multiple linear regression. In addition, classic assumption tests are also performed which include normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results of the analysis show that in the case of Bangka Belitung Islands Province, (1) the implementation of the policy had a significant effect on the welfare of the field of society; (2) Leadership has a significant effect on community welfare in education; (3) Financial Institutions have a significant effect on community welfare in education; (4) Community participation has a significant effect on community welfare in education; (5) The implementation of policies, leadership, financial institutions and community participation together have a significant effect on the welfare of the community in the field of education.